Recycling of Wood Saw Dust Waste as Green Pore Forming Agent for Porous Ceramic. Issue 1 (December 2020) - Zakaria, Siti Koriah; Hakim Md Zulkifli, Muhammad Luqman; Azhar Taib, Mustaffa Ali; Budiman, Faisal; Mohamed, Mazlan; Ali, Arlina; Yusoff, Abdul Hafidz; Teo, Pao Ter
Abstract: Porous ceramic fabrication using natural pore forming agents have received more and more attention in the past few years. However, researchers have encountered an issue with an inconsistent particle size, which led to uneven pore distribution. Considering waste material as pore forming agent, this research seeks to explore the potential application of wood sawdust in porous ceramic production. Moreover, the effects of wood sawdust weight percentage (wt.%) and firing temperature towards the physical and mechanical properties of porous ceramic will also be investigated. Porous ceramic was fabricated by introducing two different proportions of wood sawdust (10 and 20 wt.%) into China clay, followed by drying at 110°C and firing at 900°C. The characterization analyses were performed by means of Fourier Transform Infrared spectroscopy, water absorption, apparent porosity, bulk density, and X-Ray Diffraction. The results showed that the compressive strength appears to decrease as the composition of the waste wood sawdust increases. Relatively, the water absorption value increases as the wood sawdust incorporation increased. This is because more porosity formation is observed at a higher sawdust ratio, leading to a lower density of the ceramic.